Effect Of Physical Effort On Some AttackSkills And Functional Skills In Volleyball - Baqr, Najat (Journal of Physical Education, 2008)
This research aims to the following : Acquaintance with the changes occurred in the level of some attack skills for Volleyball players, before and after physical effort performance with extremely force and speed. Acquaintance with the changes occurred in the level of some functional variations before and after physical effort performance with extremely force and speed. The researcher utilized the descriptive methodology in a comparison style, because its convenience to the aims of research. Hence, the research sample is consisted of 36 volleyball players from clubs (Amanah, Karkosh, Akad, Duhok, Sulaimania and Koya). Their samples were examined with "assignable test", because they were the clubs participated in the athletic season (2006-2007). Serving test and passing test on the wall for one minute, as well as sweeping hit test and restricted physical load represented by (100 meter-Running) with maximum physical effort in the maximum speed were utilized by the researcher. Also, the necessary analysis were done. Blood samples were taken by medical staff from each player, and then transferring these samples by "Blood protectors" to the laboratory for analysis process. The most important recommendations of the researcher are as follows:- There are meaningful differences between Pre-measurement and Post-measurement for the volleyball players, Positively towards Post-measurement in both Idh and Cpk. There are no meaningful differences between Pre-measurement and Post-measurement for volleyball players with respect to sgot and sgpt.